Specific Binding of the Karyopherin Kap121p to a Subunit of the Nuclear Pore Complex Containing Nup53p, Nup59p, and Nup170p - Marelli, Marcello (The Rockefeller University Press, 1998)
We have identified a specific karyopherin docking complex within the yeast nuclear pore complex (NPC) that contains two novel, structurally related nucleoporins, Nup53p and Nup59p, and the NPC core protein Nup170p. This complex was affinity purified from cells expressing a functional Nup53p–protein A chimera. The localization of Nup53p, Nup59p, and Nup170p within the NPC by immunoelectron microscopy suggests that the Nup53p-containing complex is positioned on both the cytoplasmic and nucleoplasmic faces of the NPC core. In association with the isolated complex, we have also identified the nuclear transport factor Kap121p (Pse1p). Using in vitro binding assays, we showed that each of the nucleoporins interacts with one another. However, the association of Kap121p with the complex is mediated by its interaction with Nup53p. Moreover, Kap121p is the only β-type karyopherin that binds Nup53p suggesting that Nup53p acts as a specific Kap121p docking site. Kap121p can be released from Nup53p by the GTP bound form of the small GTPase Ran. The physiological relevance of the interaction between Nup53p and Kap121p was further underscored by the observation that NUP53 mutations alter the subcellular distribution of Kap121p and the Kap121p- mediated import of a ribosomal L25 reporter protein. Interestingly, Nup53p is specifically phosphorylated during mitosis. This phenomenon is correlated with a transient decrease in perinuclear-associated Kap121p.